The study of the reflection coefficient of a dense two-component plasma - Ashikbayeva, A.B.; Askaruly, A.; Syzganbayeva, S.A.; Mazhit, Z. (Recent Contributions to Physics, 2019)
In the work, the angular dependences of electromagnetic wave reflection coefficients from two-component dense plasmas have been investigated. The results for the dielectric function obtained in the framework of the moments method [1] and of the Mermin model’s [2] are presented in comparison with the experimental data [3-6]. In Mermin’s model both collision static and collision dynamic frequencies have been taken into account. The static characteristics of this system are designed to use the theory of linear dielectric response, where the Deutsch potential is considered as an interparticle interaction potential [7]. It is shown that, in contrast to the moment method, the Mermin model can be used only for shorter incident radiation waves of both s- and p- polarizations. On the other hand, the results obtained by the method of moments are applicable in a wider range of investigations, which concern the reflection of electromagnetic radiation from dense plasmas. In the framework of the method of moments in connection with super-intertwining chains the possible further development ways of the theory of electromagnetic waves reflection from plasmas, which use the calculation of static structural factors, have been marked.
Keywords: moment method, moments, reflection coefficient, the Mermin model, collision dynamic frequency, collision static frequency.